Brand Marketing through Customer Relationship Management - Mishra, A. K.; Pallavi (Indian Journal of Marketing, 2008)
In today’s competitive business environment, customers are making their buying decisions not just on the basis of product comparisons, but on the basis of relationships they have with the company. In fact, ensuring customer satisfaction is the key to success and companies are actively engaged in studying and exploring the conceptual foundations of managing relationships with customers. A brand derives strength from its experience with its customers and customer relationship management or CRM is all about providing customers a great experience. CRM is increasingly used to learn about customer’s needs and behaviour, as good relationship is very essential for successful brand marketing. CRM is now recognized as a powerful tool, for brand marketing to have an edge over the competitors. Customer Relationship Management is the establishment, development, maintenance and optimization of long-term mutually beneficial relationship between customers and companies. Successful CRM stresses on understanding the needs and desires of customers in order to develop stronger relationships with them. It is all about creating a competitive advantage by being the best in understanding, communicating and developing existing customer relationships along with creating and keeping new customers. CRM is immensely beneficial to the brand marketers as it helps not only in retaining customers but also enables more effective marketing. It will also result in expansion of market share and profits of the brand. A good experience of business transaction with the brand will increase the customer loyalty and tendency to purchase again and again. A bad experience with the brand, on the other hand, will transfer the company’s business to its competitors. Thus, CRM is the commitment of the brand to put customer experience at the center of its priorities.